2021
DOI: 10.1111/mec.16095
|View full text |Cite
|
Sign up to set email alerts
|

Fungal community dynamics across a forest–alpine ecotone

Abstract: Ecosystems all over the world are being affected by climate change (Parmesan, 2006;Pecl et al., 2017). High-latitude and high-altitude ecosystems are particularly exposed because of arctic amplification and elevation-dependent warming (Pepin et al., 2015;Serreze & Barry, 2011). In temperate and boreal regions, one of the most striking ecological transitions in high-elevation areas is the change from boreal lowland forests to alpine highlands without forests (Figure 1a). This marked ecotone, termed the forest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 102 publications
1
22
0
Order By: Relevance
“…Other studies at treeline indicate a decline in EcM and increase in ascomycetes from forest to tundra at the TTE (Tonjer et al, 2021). The shift from basidiomycetous, EcM‐dominated fungal communities to ascomycetous communities has been associated with the slowing of decomposition and soil C accumulation (Clemmensen et al, 2021; Tonjer et al, 2021). Together this suggests that increases in tree density and projected treeline expansion may result in rapid biogeochemical cycling associated with vegetation (Hewitt et al, in press) as observed here and soil stocks (Clemmensen et al, 2021, Tonjer et al, 2021) that are influenced by the composition of root‐associated fungi.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Other studies at treeline indicate a decline in EcM and increase in ascomycetes from forest to tundra at the TTE (Tonjer et al, 2021). The shift from basidiomycetous, EcM‐dominated fungal communities to ascomycetous communities has been associated with the slowing of decomposition and soil C accumulation (Clemmensen et al, 2021; Tonjer et al, 2021). Together this suggests that increases in tree density and projected treeline expansion may result in rapid biogeochemical cycling associated with vegetation (Hewitt et al, in press) as observed here and soil stocks (Clemmensen et al, 2021, Tonjer et al, 2021) that are influenced by the composition of root‐associated fungi.…”
Section: Discussionmentioning
confidence: 85%
“…Yet, we are not aware of studies linking their abundances to standlevel above-ground N dynamics. Other studies at treeline indicate a decline in EcM and increase in ascomycetes from forest to tundra at the TTE (Tonjer et al, 2021). The shift from basidiomycetous, EcM-dominated fungal communities to ascomycetous communities has been associated with the slowing of decomposition and soil C accumulation (Clemmensen et al, 2021;Tonjer et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While the ecology of class Archaeorhizomycetes is poorly resolved, their abundance in the soil is currently disputed. Even so, Tonjer et al (2021) reported that these root-associated ascomycetes probably promote high Carbon turnover. At the family level, we found one taxa, affiliated with degraded hemicellulose, significantly enriched in the YinC group, i.e., Pseudeurotiaceae ( Leung et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In areas with short growing seasons such as at Finse, a quick development of new leaves on deciduous shrubs is needed to reduce the risk of missing the opportunity to grow. This quick leaf development is accomplished through mobilization of belowground stored assimilates from the previous year (Karlsson, 1985;Körner and Renhardt, 1987;Tonjer et al, 2021). Although beyond the scope of this study, such below-ground responses could be explored using factorial experiments with minirhizotron tubes in climate chambers (Blume-Werry et al, 2019).…”
Section: Nee and Et Budgetsmentioning
confidence: 99%